2000
DOI: 10.1097/00000658-200001000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Tension-Free Repair of Recurrent Inguinal Hernia Under Local Anesthesia

Abstract: Given the low complication rate in this and other reported series and the absence of surgical or general complications described after preperitoneal open or laparoscopic repair and after general and spinal anesthesia, anterior mesh repair under local anesthesia seems to be a low-cost surgical technique that can be safely and effectively used even in a teaching hospital for the treatment of the majority of patients with recurrent groin hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 29 publications
1
32
1
6
Order By: Relevance
“…Gianetta et al 23 reported 2.7% scrotal hematoma, 2% cord edema, 0.7% orchitis and 0.7% wound infection. In our study, 87.7% of patients have uneventful recovery.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gianetta et al 23 reported 2.7% scrotal hematoma, 2% cord edema, 0.7% orchitis and 0.7% wound infection. In our study, 87.7% of patients have uneventful recovery.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 98%
“…In a study by Pavlidis et al 14 , the recurrence rate after tension free technique for inguinal hernia repair was as low as 1.5%. Gianetta et al 23 reported a low recurrence rate of 1.8%, Liem et al 24 reported 6% recurrence, Champault et al 25 reported 2% recurrence and the MRC Laparoscopic Groin Hernia trial Group 26 and Amid et al 3 reported as low as 0% recurrence rate after open repair of groin hernia surgeries. Our study is also consistent with these findings with a low recurrence rate of 1.75%.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…3 In addition, it carries fewer complications and has become the gold standard in open tension-free hernioplasties. 4,5 In a comparative study of open mesh techniques for inguinal hernia repair, Lichtenstein's operation was similar to mesh plug or Prolene Hernia System (PHS) repair in terms of time to return to work, complications, chronic pain, and hernia recurrence in the short term to midterm. 6 Lichtenstein's hernioplasty performed under local anesthesia has short post anesthesia recovery period, lesser complications and shorter hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies it has been documented that local anesthesia is not characterized by those complications, which generally accompany general and spinal analgesia, and does not complicate long-term treatment effects of the recurrent inguinal hernia. 3,27 In none of patients has recurrence of the hernia been observed. Regarding chronic pain, there were no statistically significant differences between the groups (P 5 0.36).…”
Section: Discussionmentioning
confidence: 97%